GREEN ECONOMY AND SUSTAINABLE DEVELOPMENT (Marketing Journal, 2025)
The article provides an in -depth analysis of the concept of green economy, its relationship with sustainable development and its impact on socio -economic systems. The main focus is on global trends, international experience and practice in the case of Uzbe kistan. The study uses theoretical, empirical, statistical and comparative analysis methods to substantiate the effectiveness of the green economy model. The conclusion provides specific recommendations for green transformation.
Keywords: green economy; sustainable development; environmental policy; energy efficiency; carbon neutrality; Uzbekistan